Self-concept on @Nge.review Instagram Account as a Representation of User Character - Sanubari, Farrasepta Deandra; Surahman, Sigit; Poetra, Yudhistira Ardi (Nyimak: Journal of Communication, 2023)
This study describes the Instagram account @Nge.review as one of the bookstagram accounts. Bookstagrammers are Instagram users who are obsessed with physical books where the object is the object in every upload on Instagram. Like other bookstagram accounts, each of these accounts has tens of thousands of followers and hundreds of uploads and, each upload has tens of thousands of likes. As one of the bookstagrammers, the owner and user here has differences with other bookstagram account users in the form of uploaded photos, the contents of the reviewed book reviews and the contents of the Instagram features contained in the account. The researcher aims to find the self-concept and character behind the habits that are shown through the contents of the account. This study uses a qualitative approach. On data search using interview techniques, observation and research documentation. Based on the research that has been done, it shows that the user as well as the owner of the @Nge.review Instagram account has a smart and imaginative self. The characters found in the user’s account that is, have an open personality.Keywords: Self concept, representation, character, Instagram ABSTRAKPenelitian ini menjelaskan akun Instagram @Nge.review sebagai salah satu akun bookstagram. Bookstagrammer adalah para pengguna Instagram yang terobsesi dengan buku fisik yang dimana benda tersebut menjadi objek dalam setiap unggahan di Instagram. Layaknya akun bookstagram lainnya, akun Instagram memiliki pengikut puluhan ribu dan ratusan unggahan serta, setiap unggahan ada yang memiliki belasan ribu likes. Sebagai salah satu bookstagrammer, pemiliki sekaligus penggunanya disini memiliki perbedaan dengan pengguna akun bookstagram lain dalam bentuk foto unggahan, isi ulasan buku yang diresensi serta, isi dari fitur-fitur Instagram yang terdapat pada akun. Peneliti bertujuan untuk mencari konsep diri dan karakter di balik kebiasaan yang diperlihatkan melalui isi dari akun tersebut. Penelitian ini menggunakan pendekatan kualitatif. Pada pencarian data menggunakan teknik wawancara, observasi dan dokumentasi penelitian. Berdasarkan penelitian yang telah dilakukan menunjukkan hasil bahwa, pengguna sekaligus sebagai pemilik akun Instagram @Nge.review memiliki diri yang pintar dan imajinatif. Karakter yang ditemukan pada pengguna akun yaitu, memiliki pribadi yang terbuka. Kata Kunci: Konsep diri, representasi, karakter, Instagram